Optimizing Customer Segments of SMEs by Transforming Business Model Canvas - Herald Galingga Wira Shenta; Fontana, Avanti (Program MM Universitas Surabaya, 2023)
This research examines the business model canvas in developing customer segments through e-commerce channels for Small and Medium Enterprises (SMEs). SMEs are expected to be sustained by reviewing their business model canvas (BMC) and finding the most potential block of BMC to be developed so that the SMEs could keep contributing to the growth of the Gross Domestic Product. However, not all SMEs have qualified managerial and technical skills to determine their potential. The BMC analysis helps SMEs to unlock their potential value. This study uses a qualitative approach by assisting one of the SMEs from Jakarta, Indonesia. The tools used to analyze are; Business Model Canvas, Porter's Five Forces, VRIO analysis, and SWOT analysis The results of the new mapping of the business model canvas by updating certain parts of the business model canvas impact increasing market access for SMEs. They can open a new paradigm for increasing SME market access, which can be done by changing one of the components of the business model canvas.